DEVELOPMENT OF CONTEXTUAL BASED PICTURE STORYBOOK MEDIA ON THEME 7 TOGETHERNESS FOR CLASS II PRIMARY SCHOOL - Nabila, Kisma; Bahri, Samsul (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This development research generally aims to develop valid, practical and effective problem-based learning tools, specifically the aim is to develop Picture Story Book Media on Theme 7 Togetherness for Grade 2 Elementary School. This research is a type of development research (Research and Development) using the 4D development model developed by Thiagarajan (1974) but modified to 3D. The 3D development model consists of define, design, and develop. This research was only carried out to the development stage because the product that has been developed is a teaching media product for reading, namely a story book equipped with pictures regarding material on theme 2 togetherness for elementary school students. The findings and discussions that have been presented have obtained several conclusions from the validity results of the picture story books that have been developed showing very valid results with a percentage of 88.2% from the validation aspects of content, language, presentation and graphics.